PHLPP2: A Prognostic Biomarker in Adenocarcinoma of the Rectum - Xie, Keju (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Adenocarcinoma of the rectum (READ) is typically diagnosed at advanced stages due to a lack of early-onset spe- cific features. Materials and Methods: The study used bioinformatics analysis of READ ribonucleic acid sequencing data from The Cancer Genome Atlas database to identify differentially expressed genes (DEGs). Overlapping genes between DEGs and autophagy-associated genes were screened for prognosis-associated DEGs, which were then validated in the OncoLnc database. Results: A total of 129 autophagy-associated DEGs were identified, with 17 genes found to be associated with READ prognosis. Multivariate Cox regression analysis revealed that only the PHLPP2 gene was significantly associated with READ prognosis (hazard ratio = 0.442, P = .026), and its low expression correlated with low survival in patients with brain lower-grade glioma (P = .00623) and pancreatic adenocarcinoma (P = .00109). Conclusions: PHLPP2 expression may serve as a READ-specific prognostic biomarker and is involved in the PI3K-Akt signaling pathway.